Pecking Order and Trade – off Capital Structure Theories in the European Countries Supported by European Stability Mechanism - Chatzinas, Georgios; Markopoulou, Maria; Papadopoulos, Simeon (European Journal of Economics and Business Studies, 2018)
The financial assistance provided by European Stability Mechanism during the recent European crisis was accompanied with severe austerity measures and strict reforms that changed significantly the economic environment in the countries that accepted it. The present study examines whether these changes affected the capital structure of the European firms in these countries. Using accounting data for firms in Cyprus, Greece, Ireland and Portugal, the researchers created a balanced panel database and applied the Shyam-Sunders and Myers (1999) methodology to investigate whether pecking order or trade-off hypotheses can better explain the financing decision of the firms in these countries during the period before and after the outset of the ESM financial assistance. The results indicate that the firms’ capital structure decisions are explained by both theories in Greece, Cyprus and Portugal before the beginning of the EMS program, while only by trade-off in Ireland. On the other hand, after the beginning of the ESM program the firms’ capital structures are better explained by trade-off hypothesis in Greece and Cyprus, while nothing changed in cases of Ireland and Portugal. The fact that Greek and Cypriot tax rates increased the most among the four examined countries may explain at least partially the above differentiations. So, the economic environment is a primary factor that affects the explanatory power of each capital structure theory. Moreover, a change in economic environment may lead to a change in the dominant capital structure theory.